Effects of methylprednisolone on exercise-induced increases of plasma levels of polymorphonuclear elastase and myeloperoxidase in man. Preliminary results - G. Camus; J. Pincemail; G. Deby-Dupont; C. Deby; A. Juchmès-Ferir; M. Lamy (Mediators of Inflammation)
The aim of the present study was to verify whether a single oral dose of methylprednisolone could modulate the exercise-induced release of polymorphonuclear neutrophil (PMN) elastase and myeloperoxidase. Four healthy, male subjects were submitted to a 20 min downhill run (−20%) at 60% VO2 max, 3 h after oral absorption of a placebo or a single dose of 32 mg methylprednisolone. A marked neutrophilia (+103% of basal PMN count; p < 0.02) was observed 3 h after methylprednisolone ingestion. During both exercise trials, placebo and methylprednisolone, PMN counts were increased by 46% and 19% (p < 0.05), respectively. The running test caused marked and significant (p < 0.05) increases in plasma myeloperoxidase concentration (MPO). The magnitude of MPO changes was the same in the two trials (+110%). Exercise also resulted in significant changes in plasma elastase concentration (EL) in both experimental conditions (placebo: +104%, p < 0.05; methylprednisolone: +338%, p < 0.005). Plasma elastase levels reached at the end of exercise on methylprednisolone were significantly higher than after placebo (p < 0.05). A significant relationship was found between EL and PMN in methylprednisolone trial only (r = 0.72; l0 < 0.005). These results showed that the transient exercise-induced release of elastase and myeloperoxidase were not decreased by methylprednisolone.